Republic of Korea : Selected Issues. (IMF Staff Country Reports; Country Report, 2018)
This Selected Issues chapter outlines a strategy to facilitate this and navigate the more challenging monetary environment, involving enhanced communication of policy interest rate intentions and inflation-forecast targeting. The reduction in the inflation target by a percentage point to 2 percent in January 2016 weakened the nominal anchor. Monetary policy can play a role rebuilding the credibility of the anchor more rapidly through the adoption of inflation-forecast targeting. This strengthening of the monetary policy framework involves enhancing communications. An effective, credible monetary policy cannot address all macroeconomic challenges facing Korea. Rather, it can foster robust growth with low inflation, providing a stable and predictable environment that allows other policies to work more effectively. These other policies play a complementary role. Fiscal policy can reinforce the effectiveness of monetary policy, as illustrated by model scenarios. Structural policies can also support monetary policy by, for example, boosting potential growth.